From intra site to macro scale GIS analysis. The work of the AeGIS Lab - Evangelidis , Vassilis; Mourthos , Yiannis; Karta , Melpomeni (Journal of Greek Archaeology, 2024)
The AeGIS Laboratory, established by the Athena Research Center in Xanthi, stands as a reflection of the enduring commitment of the Center to the realm of Geographic Information Systems (GIS) technology, dating back to 2002. This commitment has revolved around the application of GIS techniques in recording and analyzing archaeological data. By employing an array of methods including mapping, geospatial databases, photogrammetry, and archaeometry, the laboratory endeavors to equip archaeologists, historians, and cultural heritage practitioners with GIS tools for the high-resolution documentation and meticulous mapping analysis of archaeological sites and landscapes. It seeks to underscore the immense potential of GIS in addressing specific archaeological challenges by pioneering novel approaches, and to serve as a valuable resource and model for other institutions in Greece by demonstrating the transformative potential of GIS in addressing these challenges, offering a blueprint for integrating advanced digital processes in similar contexts.